Studi Literatur: Pembelajaran Konstruktif dengan Menggunakan Konten Vidio Interaktif Berbasis Budaya Tradisional - Mukhtar; Fauzi, Kms Muhammad Amin; Fadilah, Nina (Jurnal PEKA (Pendidikan Matematika), 2025)
The purpose of this study is to analyze and examine the effectiveness of learning implementation with a constructivist approach using video technology to integrate traditional culture as an effective step to increase students' ability to understand mathematical concepts. The research approach was used with literature from various relevant studies from 2019-2024. The research findings obtained are in the form of increasing student interaction and activeness in the mathematics learning process so that meaningful learning is obtained as a form of learning by integrating traditional culture as a learning medium to construct student knowledge by associating the material context close to the student's living environment, with video as an interactive media can foster a learning environment that facilitates the learning process self-sufficient. Improve students' ability to solve mathematical problems and think critically. This study also found a gap where not much research has been conducted by combining traditional cultural content with technology because there is still a lack of ability to manage learning related to technology content. This study recommends that constructive learning with traditional culture through interactive videos can be applied in the context of mathematics learning. Validate the data by comparing research results from various journals, reports, or related articles